Green, hybrid, or grey disaster risk reduction measures: What shapes public preferences for nature-based solutions?. (15th May 2022) - Anderson, Carl C.; Renaud, Fabrice G.; Hanscomb, Stuart; Gonzalez-Ollauri, Alejandro
Abstract: Nature-based solutions (NbS) contrast with grey infrastructure measures to reduce risk from natural hazards. Using natural and sustainable measures (green) or combining green with grey elements (hybrid) can provide important co-benefits beyond risk reduction. Thanks to their co-benefits and flexibility across a range of possible climate change futures, NbS are sometimes referred to as 'win-win' or 'no-regret' measures. The success of NbS and associated projects often relies on the public for co-creation, co-implementation, and long-term sustainable use, monitoring, and management. However, the relative importance of NbS benefits is defined by the perceptions and underlying values of stakeholders with potentially divergent interests. It is unclear what measures at-risk individuals may prefer on the green-hybrid-grey spectrum and what shapes their preferences, including perceived benefits and potential regret. Identifying public (mis)perceptions, expectations, objectives, and what underlies these can inform communication and project framing, engagement, and ultimately increase public acceptance and continued uptake of NbS. We use citizen surveys at three distinct European sites where NbS are being planned and in-depth focus groups as a follow-up in the site at risk of landslides (Catterline, Scotland). Preferences and their drivers for measures on the green-hybrid-grey spectrum are assessed, focusing on public perceptions of NbS effectiveness, risk, and nature. We find that although wildlife habitat and aesthetics as co-benefits are important, reducing risk is of primary concern. Uncertainty in the strength and effectiveness of NbS, as one of 13 qualitative factors we identify, drives public preferences towards hybrid measures - seen as balancing green and grey trade-offs. Misperceptions and a demand for NbS information should be addressed with experiential learning, combined with transparent two-way communication of expectations. We urge caution and further research regarding emphasizing co-benefits and the 'natural' framing of NbS when risk reduction is the primary public objective. Graphical abstract: Image 1 Highlights: Scepticism of NbS effectiveness is associated with preferences for greyer measures. Green measures are described as ideal if effective, but weaker and more uncertain. Hybrid measures favored to balance perceived trade-offs of green and grey. Public success/failure framing of NbS contradicts the no-regret/co-benefits framing. Reduce NbS uncertainty and manage expectations for lasting public acceptance.